(untitled) (GYMNASIUM, 2009)
The paper presents the factors that have an important impact on the strength of an athlete knee muscle. The paper solves a statically approach of the equilibrium of a leg, emphasizing the major influences of some variables, such as: body weight, angles of the leg with respect to earth, the length of a leg etc. The numerical results above indicate that quads need to produce much more tension than hamstrings and calves. Furthermore, the compressive force between the patella and the femur increases with increasing quads tension and increasing flexion of the knee. Repeated compressive force destroys the cartilage coating of the articulating bone surfaces, leading to frictional resistance to the sliding motion of the kneecap during knee flexion and extension.